Cultural Linguistics: The Art of Greetings in Wemale and Alune Tribes of Maluku - Wakano, Abidin; Latuapo, Ridhwan; Prihono, Eko Wahyunanto; Lapele, Fitria (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2023)
This study aims to identify and analyze cultural greetings based on the linguistic structures of the Wemale and Alune tribes in Maluku. This qualitative research employs an ethnographic approach and was conducted across eight sub-districts in Western Seram Regency, Maluku Province. Data collection methods included observation, interviews, and Focus Group Discussions (FGD). Data analysis followed Spradley's model, which comprises four phases: domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The study identified 20 traditional greetings from the indigenous peoples in the Western Seram Regency. Ten of these greetings were recommended for official use, and six were selected as the primary cultural greetings based on the linguistic structures of the Wemale and Alune tribes. These greetings are Ho Salamate, Sou Salamate, Tabea Salamate, Mese, Upu Ana, and Sopai. This research contributes to the preservation and revitalization of the Wemale and Alune languages by proposing standardized cultural greetings that reflect the linguistic and cultural heritage of these tribes. The findings also support the integration of these greetings into local education curricula to promote cultural sustainability.